Ideology of Galician Nationalism from mid-1910 through 1920s: A Nosa Terra Newspaper - Maksim V. Kirchanov (СибСкрипт)
A Nosa Terra was the major newspaper and the ideological mouthpiece of Galician political, cultural, and ethnic nationalism in the mid-1910s and 1920s. The principles of interdisciplinary historiography made it possible to analyze Galician nationalism as a social, intellectual, political, or cultural phenomenon, i.e., the history of Galician nationalistic ideology as a factor in the local intellectual history. Galician nationalists had a great impact on the subsequent period radicalization of nationalism. The article covers the following issues: 1) the main points in the history of nationalism from mid-1910s through 1920s, 2) the role of intellectuals in the development and transformation of Galician nationalism, 3) the political program proposed by nationalist activists, 4) the ideological concepts and constructs coined by nationalist intellectuals for the development of Galician ethnicity, language, and culture, 5) the role of nationalistic ideological concepts in the general history of Galician nationalism. The ideological activities of Galician nationalists in the mid-1910s–1920s became an important stage in the intellectual history of nationalism in Galicia, predetermining its future development to the moment when Spanish Francoism marginalized all regional nationalisms, including Galician.